Framing Media Online Terhadap Puan Maharani Sebagai Bakal Calon Presiden Dalam Pemilihan Presiden 2024 - Muhammad Balya; Varinia Pura Damaiyanti (Huma: Jurnal Sosiologi, 2023)
Puan Maharani is often in the media spotlight and public perception of her is influenced by positive or negative online media coverage, depending on the political interests and public perception of her policies or actions. The purpose of this study is to analyze the influence of online media in shaping public perception of Puan Maharani, especially in the context of the 2024 presidential election. The research used a descriptive qualitative approach by applying the framing analysis model of Pan and Kosicki and data collection techniques from four online media (two national and two regional) during the period of November 1st to December 31st, 2022. The results of the analysis show a tendency of positive framing towards Puan Maharani. However, there are differences in the way positive narratives are built between two regional online media and national online media. Two regional online media tend to use exaggerated narratives such as hyperbole sentences in building positive narratives about Puan Maharani, while national online media are more varied in framing and minimize excessive rhetoric in building narratives about Puan Maharani. Despite the political interests of online media in creating news, national online media appears to be more objective in providing information about Puan Maharani. Online media has a significant influence in shaping public perception of Puan Maharani, especially in the politics of the 2024 presidential election. Positive framing may provide advantages, while framing that is diverse and minimizes excessive rhetoric tends to be more objective.